Evaluation of soaking to recover trace DNA from fired cartridge cases. Issue 5 (3rd September 2021) - Prasad, Elisha; Barash, Mark; Hitchcock, Catherine; van Oorschot, Roland A. H.; Raymond, Jennifer; McNevin, Dennis; Gunn, Peter
ABSTRACT: The recovery of trace DNA from cartridge cases is of common interest across many jurisdictions. Soaking offers improved profiling success rates over traditional methods. We evaluated the effects of firing, calibre, and metal composition on controlled and handled DNA samples utilizing a soaking method. Our results show that firing decreases the quantities of DNA recoverable from cartridge cases and higher quantities of DNA are recoverable from nickel ammunition compared to brass. In spiked samples, calibre of ammunition had no significant effect on DNA recovery. Despite slight to moderate DNA degradation and variable profiling success rates, spiked unfired and fired nickel cartridges resulted in more usable profiles than brass cartridges. These findings can aid in triaging the types of ammunition subjected to DNA testing.